A Sketch of the Causes, Operations and Results of the San Francisco Vigilance Committee of 1856 - Webb, Stephen Palfrey, 1804-1879 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Sketch of the Causes, Operations and Results of the San Francisco Vigilance Committee in 1856" by Stephen Palfrey Webb is a historical account written in the late 19th century. This book explores the emergence and activities of the Vigilance Committee in San Francisco, which arose in response to rampant crime and corruption in the city during a period marked by the Gold Rush and a chaotic influx of settlers. Webb, who served as Mayor of San Francisco during the events he chronicles, provides firsthand insights into the societal conditions that led to the formation of this self-imposed law enforcement group. In this comprehensive recounting, Webb details the corrupt political landscape of San Francisco in the 1850s, including the violent crime sprees and public outrage that culminated in the assassination of newspaper editor James King of William. In the wake of his murder, citizens took it upon themselves to create the Vigilance Committee, which aimed to restore order through direct action against criminals and corrupt officials. The Committee administered its own brand of justice, including trials and executions of those deemed guilty. Webb emphasizes the moral complexities and justifications for the Committee$1 (Bs actions, reflecting on the dire circumstances that pushed ordinary citizens to take drastic measures to seek justice when the established legal system failed them. Through a detailed narrative, Webb captures the tumultuous spirit of the time and the community's quest for security and equity amid lawlessness. (This is an automatically generated summary.)s
Release date is 2004-06-01
Produced by David Schwan, and David Widger
Keywords: San Francisco Committee of Vigilance of 1856